1998
DOI: 10.2105/ajph.88.10.1523
|View full text |Cite
|
Sign up to set email alerts
|

Does passive smoking in early pregnancy increase the risk of small-for-gestational-age infants?

Abstract: OBJECTIVES: This study tested the hypothesis that women who deliver small-for-gestational-age infants are more often exposed to passive smoking at home or at work. METHODS: Among a 1-year cohort of nulliparous women in the city of Malmö, Sweden 872 (87.7%) women completed a questionnaire during their first prenatal visit. The study was carried out among women whose pregnancies resulted in a singleton live birth (n = 826), 6.7% of infants were classified as small for their gestational age. RESULTS: Passive smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 28 publications
2
27
1
1
Order By: Relevance
“…This is in agreement with the hypothesis that maternal smoking reduces the risk of pre-eclampsia and has a mechanism of causing FGR which is independent of blood pressure [28][29][30] . Numerous prior researches supported the association between passive smoking and fetal growth [31,32] , but that was not supported by our findings; however, recall bias and underreporting of the risk factor cannot be excluded.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in agreement with the hypothesis that maternal smoking reduces the risk of pre-eclampsia and has a mechanism of causing FGR which is independent of blood pressure [28][29][30] . Numerous prior researches supported the association between passive smoking and fetal growth [31,32] , but that was not supported by our findings; however, recall bias and underreporting of the risk factor cannot be excluded.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, particulate air pollution from combustion sources shares many characteristics with sidestream tobacco smoke, which is rich in particles and polycyclic aromatic hydrocarbons. A number of studies (Ahluwalia et al, 1997;Dejin-Karlsson et al, 1998;Dejmek et al, 2002;Kharrazi et al, 2004) found that environmental tobacco smoke was associated with low birth weight, small-for-gestational age, and preterm delivery. This provides support for the plausibility of the reported association.…”
Section: Prenatal Effectsmentioning
confidence: 99%
“…Some of these studies have used questionnaire data to determine ETS exposure ( Martin and Bracken, 1986;Chen et al, 1989;Mathai et al, 1992;Fortier et al, 1994;Roquer et al, 1994;Dejin -Karlsson et al, 1998), with five studies relying solely on information concerning household members who smoke, one as recently as 1997 (Brooke et al, 1989;Chen et al, 1989;Mathai et al, 1992;Saito, 1991;Ahluwalia et al, 1997 ). Other studies examining the association between ETS exposure and low birth weight have measured exposure using a biomarker such as cotinine (Eskenazi et al, 1995;Haddow et al, 1988;Peacock et al, 1988 ).…”
Section: Introductionmentioning
confidence: 99%